Effects of annealing on the magnetic properties and magnetocaloric effects of B doped Ni-Mn-In melt-spun ribbons - Pandey, Sudip (2018)
The magnetic, structural, thermal, and magnetocaloric properties of Ni50Mn35In14.5B0.5 melt-spun ribbons have been studied through X-ray diffraction (XRD), differential scanning calorimetry, and magnetization measurements. A comparison of magnetic properties and magnetocaloric effects (MCE) of Ni50Mn35In14.5B0.5 melt-spun and annealed ribbons to its bulk form has been shown in detail. We have observed that a short time vacuum annealing (1073 K-10 min) on ribbon sample can restore the properties of the bulk material. Significant changes in magnetic and magnetocaloric properties have been observed between Ni50Mn35In14.5B0.5 ribbons in the as-solidified state and after thermal annealing. The MCE parameters of annealed ribbons were found to be comparable to those observed in the bulk alloy. The maximum value of relative cooling power of 150 J/kg for a magnetic field change of 5 T was found at the martensitic transition for annealed ribbons. The working temperature range of the magnetic entropy change (ΔSM) for annealed ribbons has been significantly enlarged in comparison to melt-spun ribbons. The role of the magnetic and structural changes on the transition temperatures of the ribbons is discussed.